THU0117 Low-Risk Patients Also Benefit from Remission Induction Treatment in Early Rheumatoid Arthritis: Week 52 Results from the Carera Trial. (9th June 2015) - De Cock, D.; Corluy, L.; Joos, R.; Langenaken, C.; Taelman, V.; Raeman, F.; Ravilingien, I.; Vandevyvere, K.; Lenaerts, J.; Geens, E.; Geusens, P.; Vanhoof, J.; et al.
Abstract : Background: Early intensive treatment to target is recommended in severe early Rheumatoid Arthritis (eRA). However, data are lacking in patients presenting without markers of poor prognosis. Objectives: To compare Methotrexate (MTX) with or without Glucocorticoid (GC) remission induction in a tight control setting over 52 weeks in low-risk patients with eRA. Methods: CareRA is a two year prospective investigator-initiated multicenter RCT rooted in daily practice. DMARD naïve eRA patients were stratified into a high or low-risk group according to classical prognostic markers (presence of erosions, rheumatoid factor, anti-cyclic citrullinated protein and disease activity). In the low-risk arm, 43 patients were randomized to 15mg MTX monotherapy following a Tight Step Up (MTX-TSU) approach and 47 patients to a Cobra Slim schedule (MTX+30mg prednisone tapered to 5mg daily from W6). GCs were tapered from W28 and stopped at W34. A predefined treat to target approach was applied. Efficacy measures were proportions of DAS28(CRP) remission, good EULAR response, clinically meaningful HAQ response, HAQ=0 and Area Under the Curve (AUC) for DAS28(CRP) (ITT analysis). Radiographic progression was measured via the Sharp Van der Heijde (SvH) method. Adverse events related to therapy (AEs) were registered. No power was calculated in this explorative study. Missing data were imputed via last observation carried forward. Results: Remission rates at week 52 were 57.4% and 67.4% in the MTX-TSU and Cobra Slim group respectively (p=0.329). MTX-TSU patients had a higher AUC for DAS28(CRP) than Cobra Slim patients over 52 weeks of treatment (p=0.017). No other efficacy scores differed between groups. 76% of X-ray images were available at baseline. Radiographic progression was minimal. SvH scores were 0.7±1.1 and 0.9±1.5 at baseline and changed over 52 weeks 0.2±0.3 and 0.3±0.4 in the MTX-TSU and Cobra Slim group respectively (p=0.184). The numbers of AEs were 48 in 27 MTX-TSU patients and 49 in 20 Cobra Slim patients (p=0.871). Two serious AEs (pulmonary infection and anemia) were registered in the Cobra Slim group. We observed numerically more treatment adaptations and IM/IA GC injections in MTX-TSU patients. Conclusions: Both RA therapies achieved high remission rates in a tight control setting at week 52. However, remission induction with Cobra Slim resulted in a more rapid and sustained disease control. MTX with or without GC remission induction showed a comparable safety profile. Disclosure of Interest: None declared